DETERMINANTS OF STUDENT HOUSING SELECTION DECISIONS: AN ANALYSIS OF THE ROLE OF ECONOMIC STATUS AND LIFESTYLE - Valentina, Valentina; Andriyansyah, Muhamad (Edunomika Journal : Studies In Education And Development Economics, 2026)
This study aims to analyze the determinants of boarding house purchasing decisions among university students, focusing on the influence of parental economic status and lifestyle. Amidst increasing global educational mobility, understanding student consumption behavior is crucial for the development of the educational property industry. Using a descriptive quantitative approach, this study involved 82 students of the Economics Education Study Program at the University of Jambi who were selected through a total sampling technique . Data were collected through a structured questionnaire and analyzed using multiple linear regression. The research findings indicate that partially, economic status and lifestyle have a positive and significant effect on purchasing decisions. Simultaneously, both variables contribute 34.1 % to the stability of students' housing choices. Interestingly, the lifestyle variable was found to have a more dominant influence (t-test 5.595) than economic status (t-test 2.126), indicating that subjective value orientation and social identity are prioritized over budgetary rationality. The novelty of this study lies in identifying the phenomenon of inconsistent economic behavior of students, where academic knowledge of economics is often distorted by the demands of a modern lifestyle which triggers a high frequency of residential changes. The implications of this research emphasize the need for boarding house providers to adapt digital and social lifestyle-based facilities. Theoretically, this study contributes to the development of consumer behavior theory by emphasizing lifestyle's role as a critical moderator of economic decisions in academic settings.